Implementation of land reform policy with special reference to the Capricorn District in the Limpopo Province of South Africa - Machaka, Matome Eric (University of Limpopo, 2007)
Refer to the document
Thesis (MPA.) -- University of Limpopo, 2007
Keywords: Land reform; Land ownership; Land reform policy; Land reform -- South Africa